INCREASING MATHEMATICS LEARNING OUTCOMES USING REALISTIC MATHEMATICS EDUCATION - Eka Putri Nurjanah; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The problem that underlies this research is the low value of learning outcomes of students, especially in class VII D. This study aims to improve the learning outcomes of students by using a realistic mathematics education approach to students of class VII D in State Junior High School (SMP Negeri) 2 Bambanglipuro even semester 2017 Academic Year / 2018. This study includes Classroom Action Research (CAR). The research was conducted in two cycles. Each cycle consists of two meetings. Data collection techniques used are interviews and tests. Data analysis used is data reduction, data presentation, conclusion, and verification. The indicator of the success of this study is the achievement of increased learning outcomes of students. Learning outcomes of students are obtained from the work of solving the description questions. This success is shown by students' learning outcomes achieving an average good category (â‰¥ 61%). Based on the study results using a realistic mathematics education approach in the quadrilateral sub-topic, there is an increase in students' learning outcomes. This is evident from the first cycle test results to the second cycle test, which has increased by 1.76%. In the first cycle, the average test results of students were 42.47. In the second cycle, the average test results of students were 43.22. However, there has been an increase in learning outcomes but has not met the indicators of success.